2020
DOI: 10.1007/s40123-020-00244-y
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Corneal Fibrosis After Descemet’s Stripping Automated Endothelial Keratoplasty: A Case Report

Abstract: Purpose: To report the resolution of anterior corneal fibrosis after Descemet's stripping automated endothelial keratoplasty (DSAEK), in a patient with chronic corneal edema and anterior stromal scarring. Methods: A 63-year-old woman, with a history of Fuchs endothelial dystrophy, presented with increasing discomfort and gradual visual loss in her right eye. Clinical examination revealed longstanding bullous keratopathy accompanied by marked subepithelial fibrosis (SEF). Based on the low postoperative visual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, in case 1, by prescribing Ripasudil after surgery, the corneal edema was almost completely solved, but the usual PBK sequelae, such as sub-epithelial fibrosis, could not be avoided furtherly. Since a slowly recover and regression of fibrosis has been proven after corneal endothelial lamellar surgery, 11 ut-DSAEK has been performed to maximize visual outcomes in such patient. Case 2 and 3 were both at high risk of disease progression after cataract surgery according to corneal pachymetry and IVCM assessments.…”
Section: Discussionmentioning
confidence: 99%
“…However, in case 1, by prescribing Ripasudil after surgery, the corneal edema was almost completely solved, but the usual PBK sequelae, such as sub-epithelial fibrosis, could not be avoided furtherly. Since a slowly recover and regression of fibrosis has been proven after corneal endothelial lamellar surgery, 11 ut-DSAEK has been performed to maximize visual outcomes in such patient. Case 2 and 3 were both at high risk of disease progression after cataract surgery according to corneal pachymetry and IVCM assessments.…”
Section: Discussionmentioning
confidence: 99%
“…A number of explanations for this can be suggested, but the mechanism remains to be elucidated. Interestingly, Zola et al 7 demonstrated improved corneal clarity and reduced density of anterior subepithelial fibrosis following endothelial keratoplasty in non-aniridic eyes. They proposed a cascade of corneal remodeling following resolution of stromal edema after Descemet stripping automated endothelial keratoplasty, amongst other factors, as a possible mechanism for this improvement, which suggests that a similar interaction could be the reason behind the great improvement seen in our case.…”
Section: Discussionmentioning
confidence: 99%